2015
DOI: 10.3390/su70912425
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the Gender Gap and Low Employment of Female Workers in a Stratified Labor Market: Evidence from South Korea

Abstract: The gender gap in working conditions has barely improved in South Korea where various measures for gender equality have been in place for a relatively long time. Furthermore, the female employment rate is also the lowest in OECD (Organization for Economic Cooperation and Development) countries. This study will evaluate the stratified structure of the labor market to identify the causes and will analyze changes in the gender employment distribution and mobility. This study conducted an empirical analysis of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Some studies determined that the non-economically active population more than doubled for women compared to men, and women were also more likely to be employed in the relatively weak peripheral labor market in South Korea [42,43]. Thus, the empirical results in this study reflect the phenomenon explained by previous studies.…”
Section: Resultssupporting
confidence: 73%
“…Some studies determined that the non-economically active population more than doubled for women compared to men, and women were also more likely to be employed in the relatively weak peripheral labor market in South Korea [42,43]. Thus, the empirical results in this study reflect the phenomenon explained by previous studies.…”
Section: Resultssupporting
confidence: 73%
“…Although several countries have implemented gender equality policies, the results have often been disappointing [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent studies, non-regular workers mostly have poorer working conditions in terms of wages, additional wages, employee benefits, and social security as well as job stability than do regular workers. Furthermore, it is not easy to transition from non-regular employment to regular employment, which tends to be increasingly firmly entrenched [9]. Even in the public sector, a large gap is evident in working conditions between non-regular and regular workers, such as in wages and employee benefits, and it was found that they are frequently given unreasonable work orders [10].…”
Section: Introductionmentioning
confidence: 99%